Surface Engineering of Ceramic Nanomaterials for Separation of Oil/Water Mixtures - Zulfiqar, Usama; Thomas, Andrew G.; Matthews, Allan; Lewis, David J. (Frontiers in Chemistry, 2020)
Oil/water mixtures are a potentially major source of environmental pollution if efficient separations technology is not employed during processing. A large volume of oil/water mixtures are produced via many manufacturing operations in food, petrochemical, mining and metal industries and can be exposed to water sources on a regular basis. To date, several techniques are used in practice to deal with industrial oil/water mixtures and oil spills such as in situ burning of oil, bioremediation and solidifiers which change the physical shape of oil as a result of chemical interaction. Physical separation of oil/water mixtures is in industrial practice, however, the existing technologies to do so often require either dissipation of large amounts of energy (such as in cyclones and hydrocyclones) or large residence times or inventories of fluids (such as in decanters). Recently, materials with selective wettability have gained attention for application in separation of oil/water mixtures and surfactant stabilized emulsions. For example, a superhydrophobic material is selectively wettable towards oil whilst having poor affinity for the aqueous phase, therefore a superhydrophobic porous material can easily adsorb the oil while completely rejecting the water from an oil/water mixture, thus physically separating the two components. The ease of separation, low cost and low energy requirements are some of the other advantages offered by these materials over existing practices of oil/water separation. The present review aims to focus on the surface engineering aspects to achieve selectively wettability in materials and its relationship with the separation of oil/water mixtures with particular focus on emulsions, on factors contributing to their stability and how wettability can be helpful in their separation. Finally, the challenges in application of superwettable materials will be highlighted and potential solutions to improve the application of these materials will be put forward.